Philosophical Distinction of Tabarru' (Wadiah) and Muawadhah (Sale and Purchase) Contracts: Analysis of Mawdu'i Interpretation and Its Implications for Modern Islamic Banking Products - Vico Dwi Yustianto; Saberi Othman; Bayram Costu (INSANI: Jurnal Ilmu Agama dan Pendidikan, 2026)
This study aims to fundamentally distinguish the concepts of Wadiah (deposit) and Bay’ (sale and trade) through the perspective of Al-Qur'an and Hadith studies. In modern Islamic banking practices, the boundaries between Wadiah which serves as a social contract of safekeeping and Bay’ which focuses on commercial profit are often blurred, particularly in savings products that offer bonuses resembling investment returns. Utilizing a qualitative method with a Tafsir Mawdu'i (thematic exegesis) approach, this research analyzes verses and traditions related to amanah (trust) and tijarah (trade). The study employs content analysis to examine classical interpretations (Turats) and juxtapose them with contemporary financial practices. The findings reveal that the Al-Qur'an establishes a strict ontological separation between safekeeping and exchange contracts. Wadiah is constructed upon the preservation of assets without the guarantee of return, whereas Bay’ is permissible only under the principle of mutual consent and risk-taking. This research implies that hybrid contracts in Islamic banking must be re-evaluated to ensure they do not violate the core textual evidences (Nash), preserving the sanctity of Wadiah from hidden usurious elements found in profit-seeking transactions.